The influence of brand attitude and e-wom on brand loyalty with consumer brand identification as a mediation variable - Rini Sarianti; Natasha Alivia (Universitas Negeri Padang, 2021)
The purpose of this study was to analyze: (1) the influence of Brand Attitude on Brand Loyalty, (2) the influence of electronic word of mouth on Brand Loyalty, (3) the influence of Brand Attitude on Consumer Brand Identification, (4) the influence of electronic word of mouth on Consumer Brand Identification, (5) the influence of Consumer Brand Identification on Brand Loyalty, (6) The influence of Brand Attitude on Brand Loyalty through Consumer Brand Identification, (7) The Influence of electronic word of mouth on Brand Loyalty through Consumer Brand Identification. This type of research is causative research. The population in this study were female students in the city of Padang who used Emina's products. The total sample of this study was 160 people by using online questionnaire. The analysis technique in this study uses the PLS-SEM analysis method. Based on the result of data processing that has been found, the result of hypothesis testing shows that brand attitude, electronic word of mouth and consumer brand identification positively affects on brand loyalty. Also brand attitude and electronic word of mouth positively affects on consumer brand identification. Furthermore, Brand Attitude and electronic word of mouth positively affects on brand loyalty through consumer brand identification. For the future research it is better to explore more about variable that can influence brand loyalty.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//